Patterns of thermal adaptation in a globally distributed plant pathogen: Local diversity and plasticity reveal two‐tier dynamics. Issue 1 (26th January 2022) - Boixel, Anne‐Lise; Chelle, Michaël; Suffert, Frédéric
Abstract: Plant pathogen populations inhabit patchy environments with contrasting, variable thermal conditions. We investigated the diversity of thermal responses in populations sampled over contrasting spatiotemporal scales, to improve our understanding of their dynamics of adaptation to local conditions. Samples of natural populations of the wheat pathogen Zymoseptoria tritici were collected from sites within the Euro‐Mediterranean region subject to a broad range of climatic conditions. We tested for local adaptation, by accounting for the diversity of responses at the individual and population levels on the basis of key thermal performance curve parameters and "thermotype" (groups of individuals with similar thermal responses) composition. The characterization of phenotypic responses and genotypic structure revealed the following: (i) a high degree of individual plasticity and variation in sensitivity to temperature conditions across spatiotemporal scales and populations; and (ii) geographic variation in thermal response among populations, with major alterations due to seasonal patterns over the wheat‐growing season. The seasonal shifts in functional composition suggest that populations are locally structured by selection, contributing to adaptation patterns. Further studies combining selection experiments and modeling are required to determine how functional group selection drives population dynamics and adaptive potential in response to thermal heterogeneity. Abstract : We investigated the diversity of thermal responses in fungal plant populations sampled within the Euro‐Mediterranean region. We highlighted (i) a high degree of individual plasticity and variation in sensitivity to temperature conditions across spatiotemporal scales and populations; and (ii) geographic variation in thermal response among populations, with major alterations due to seasonal patterns. The seasonal shifts in functional composition suggest that populations are locally structured by selection and thus reveal two‐tier adaptive dynamics.